The Modern Nile Delta Continental Shelf, with an Evolving Record of Relict Deposits Displaced and Altered by Sediment Dynamics - Omran E. Frihy; Jean-Daniel Stanley (Geographies, 2023)
The most extensive coverage of surficial sediment samples collected to date on Egypt’s Nile Delta coast and shelf is needed to better define sediment dispersal patterns across this setting’s rapidly eroding margin. Changes in time are now induced by River Nile sediment cutoff by dams, sea level rise, marked shelf subsidence, and regional climate changes, which have altered the amounts and components of sediments; these require replacement, along with the implementation of more effective coastal protection measures. Multiple computer-generated offshore maps depict the distributions and proportions of sand, silt, and mud; the mean grain size and standard deviation (sorting); heavy mineral concentrations; and carbonate content. Heavy mineral lobes at the coast and offshore identify former Nile branch sites. Channel lobes extending seaward resulted from their progradational phase and from the delta’s altered sedimentation from the early to late Holocene. The progressive deposition and erosion of these fossil fluvial lobes, and of two active Nile channels, selectively removed their quartz and less dense minerals, thus concentrating heavy minerals on the coast and inner shelf. The prolonged dispersal of original sediment effluence from relict and recent Nile tributaries induced variable depositional patterns on the present shelf. These coastal depocenters, along with extensive sand, silt, and mud from shelf sediments, were reworked further seaward and dispersed by bottom currents, thus masking most previous onshore-to-offshore transport patterns. The major surficial features document long-term responses to the diverse dispersal that influenced the shoreline to the outer shelf deposits from the Pleistocene to the present.